Active site directed chemical modification of alpha-galactosidase from bacillus stearothermophilus (NCIM 5146): involvement of lysine, tryptophan and carboxylate residues in catalytic site - Gote, M. M.; Khan, Mohammad Islam; Khire, Jayant Malhar (Enzyme and Microbial Technology, 2007)
The catalytic amino acid residues of the extracellular a-galactosidase (alpha-D-galactoside galactohydrolase; EC 3.2.1.22) from Bacillus stearothermophilus NCIM 5146 were investigated by pH dependence and chemical modification studies. These results suggested that carboxylate and a lysine residue take part in catalysis and only lysine residues were essential for substrate binding. Carbodiimide mediated chemical modification of the enzyme also supported that a carboxylate residue located in the active site act as a nucleophile base in substrate cleavage. Acylation and reductive methylation of lysine residues by acetic, citraconic anhydride and sodium borohydride suggested that four protonated lysine residues carrying positive charge on its epsilon-amino group provides the positive charge density for binding of the substrate. Additionally four tryptophan residues also found near to the active site and in a moderately hydrophobic environment. Kinetic and thermal inactivation study of modified enzyme indicated that these tryptophan residues might have a role in the catalytic site as well as in the thermal stabilization of active site conformation at higher temperature. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Active site; alpha-galactosidase; Bacillus stearothermophilus; carboxylate; Chemical modification; lysine; Tryptophan